Sustainable diets and biodiversity: Directions and solutions for policy, research and action - Burlingame, B.; Dernini, S.; Food and Agriculture Organization of the United Nations; Bioversity International (2012)
This book presents the current state of thought on the common path of sustainable diets and biodiversity. It consists of 4 chapters which look at sustainable diets and biodiversity through sustainable food production and consumption which is illustrated with ten cases studies. The final chapter deals more specifically with the example of the Mediterranean diet. The book resulted from an International Scientific Symposium “Biodiversity and Sustainable Diets: United Against Hunger” organized jointly by FAO and Bioversity International, held at FAO, in Rome, from 3 to 5 November 2010, within the World Food Day/Week programme, on the occasion of the 2010 International Year of Biodiversity. Book by chapters: Introduction Chapter 1 - SUSTAINABLE DIETS AND BIODIVERSITYChapter 2 - SUSTAINABLE FOOD PRODUCTION AND CONSUMPTIONChapter 3 - CASE STUDIES: BRINGING BIODIVERSITY TO THE PLATEChapter 4 - AN EXAMPLE OF A SUSTAINABLE DIET: THE MEDITERRANEAN DIET